Location, Location, Location: David Ross McCord and the Makings of Canadian History - Harvey, Kathryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2008)
AbstractThis study of the McCord National Museum in Montreal examines the role of place in the creation of personal and public memory. The founder, David Ross McCord, sought to promote a version of Canadian history in which family and personal myth were conflated with that of nation. McCord’s highly personal narrative of Canadian origins was conceived in the private space of the home and was made manifest through the repetitive act of remembering.